Research on Contract Coordination in the Manufacturing Supply Chain Given China’s Work Safety Constraints - Zongkang Yang; Qiang Mei; Qiwei Wang; Suxia Liu; Jingjing Zhang (Complexity)
With supply chain management’s increasing importance in work safety, this paper establishes the leading enterprise with core enterprises as work safety units. These guide the small and medium-sized enterprises within the supply chain to focus on improving work safety according to the leading position of the supply chain’s core enterprises. Therefore, the Stackelberg game model is applied to build and explain supply chain node-enterprises’ optimal centralized and decentralized operational decisions. This research was conducted in the context of enterprise work safety constraints’ influence on the manufacturing supply chain’s equilibrium results. It also reveals the necessity in supply chain node enterprises’ contract coordination design by comparing the two decision models’ equilibrium results. Ultimately, the manufacturing supply chain’s overall profit and work safety can reach a level that includes centralized decisions through revenue- and cost-sharing contracts. Furthermore, profits to the supply chain’s node enterprises also improve, and a Pareto optimality is achieved. An enlightened management demonstrates the importance of core enterprises’ leading position in the supply chain, and the supply chain node enterprises’ levels of work safety, product demand, and total profit can be promoted through revenue- and cost-sharing contracts.